DIGITAL MARKETING MELALUI PEMBUATAN KONTEN PADA MEDIA SOSIAL SEBAGAI PENINGKATAN PROMOSI DAN BRANDING SEKOLAH - Putra, Yudithia Dian; Kustiawan, Usep; Pramono, Pramono; Salehuddin, Shafira Nurulita; Putri, Novenda Cahya Awika (Jurnal AbdiMas Nusa Mandiri, 2025)
Digital marketing has become one of the forms of marketing by utilizing digital platforms and technologies to connect with the target audience online. The use of digital marketing can be applied through digital-based media. Social media is integrated with various lines and used as a means of disseminating relevant content according to the target audience in achieving the organization's vision, mission, and goals. Based on the observation results, many teachers still have limited skills in creating digital content and marketing content. Therefore, the purpose of this community service activity is to enhance the marketing skills of teachers and educational staff through e-marketing-based activities for school social media. This community service activity was conducted in the Auditorium of Campus 3, Universitas Negeri Malang, Kepanjen Kidul, Kota Blitar. The partners in this community service activity are the PAUD teachers of Group 3, Kepanjen Kidul, Blitar City. The implementation method consists of three stages: needs analysis, execution, and evaluation. The result of the implementation of this program is content published in each institution as a means of promotion and branding. In addition, the PAUD teachers of Cluster 3 Kepanjen Kidul, Blitar City, gained knowledge and understanding both theoretically and practically, including understanding branding, design skills, website utilization, institutional branding enhancement, and skill sustainability. This understanding is expected to be continuously applied as an effort to optimize digital skills in the context of school branding at the early childhood education level.